2019
DOI: 10.1097/iae.0000000000002351
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Endophthalmitis After Intravitreal Injection With Bevacizumab, Aflibercept, and Ranibizumab

Abstract: Purpose: To determine whether sterile preloading of anti–vascular endothelial growth factor agents reduces the risk of postintravitreal injection endophthalmitis. Methods: This is a retrospective cohort study using medical claims data from a large, national US insurer. Cohorts were created using intravitreal injections of anti–vascular endothelial growth factor injections from 2005 to 2016. For inclusion, patients had to have at least 6 months of data b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 28 publications
7
33
0
Order By: Relevance
“…More importantly however, even after accounting for this temporal change, compounded bevacizumab still conferred a protective effect compared to office-loaded syringes. 2 Baudin et al and our studies also found a 29% and 30% increased risk of endophthalmitis in women, repsectively. 1,2 These represent the first reports linking gender to endophthalmitis rates.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…More importantly however, even after accounting for this temporal change, compounded bevacizumab still conferred a protective effect compared to office-loaded syringes. 2 Baudin et al and our studies also found a 29% and 30% increased risk of endophthalmitis in women, repsectively. 1,2 These represent the first reports linking gender to endophthalmitis rates.…”
supporting
confidence: 80%
“…2 Baudin et al and our studies also found a 29% and 30% increased risk of endophthalmitis in women, repsectively. 1,2 These represent the first reports linking gender to endophthalmitis rates. Interestingly, despite age, gender and race almost uniformly being controlled for in other ophthalmic assessments (even when no demonstrable link exists to do so), gender has often been over-looked with regards to endophthalmitis after intravitreal injections.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Large, prospective, industry-sponsored trials on more than 7000 intravitreal anti-VEGF injections have found the incidence to range from 0.05% to 0.09%. 16,17 A recent large retrospective study using nationwide medical claims data on more than 1 million anti-VEGF injections reported an incidence of 0.035%, 18 whereas smaller studies at a single institution have yielded higher incidences of 0.10%. 11 Most data on postinjection endophthalmitis have been collected from institutions where attending surgeons perform all procedures, with only a few studies analyzing institutions where trainees play a role in performing injections.…”
Section: Discussionmentioning
confidence: 99%